Influence of Preliminary Combined Loading on Low Cyclic Fatigue Deformation of Aluminum Alloy D16ChATV. (2015) - Hutsaylyuk, Volodymyr; Snieżek, Lucjan; Torzewski, Janusz; Chausov, Mykola; Berezin, Valentin; Pylypenko, Andrii
Abstract: The article presents the research results of a D16ChATV aluminum alloy in preliminary combined loading conditions. Examination of samples was carried out by imposing additional force impulse at the monotonic tension at the stage of elastic deformation. The material modified in this way, was also subjected to fatigue testing in a low cycle fatigue loading conditions. Loading applied during the tests was oscillating sinusoidal, with the strain ratio of R=-0.2 and controlled strain amplitude ɛac =const. As a result of studies it was found, that in preliminary combined loading conditions in the test samples a processes occur related to the rapid dissipation of energy, leading to the modification of the mechanical properties of the test material. During imposing of the additional force impulse a single pulsed loading are formed the plastic zones of varying scope in the specimen made from aluminum alloy. The strength of D16ChATV aluminum alloy under a low cycle fatigue loading of the preliminary combined loading is characterized by a small increase or remains at basic level.